Encounters with the Holy : a Conversational Model for Worship Planning. - Miller, Barbara Day, 1946- (Vital worship, healthy congregations series., 2010)
Many churches have active worship committees or planning teams, and an abundance of books and resources guide pastors and laity. Encounters with the Holy offers a conversational model of worship planning that was developed to train practitioners to be more reflective in their planning of worship experiences. The model planning, ordering, worshiping, reflecting is a flexible, fluid pattern. It provides a more circular, spiraling practice of imaginative planning, preparing the leaders and the space, and reflecting theologically to understand more fully the experience of worship. It has been test.